2016
DOI: 10.3329/pa.v27i2.29328
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Pasteurella multocida Type B causing haemorrhagic septicemia in cattle and buffaloes of Bangladesh

Abstract: Hemorrhagic septicemia (HS) is an acute septicemic disease that primarily affects cattle and buffaloes. The disease is caused by Pasteurella multocida sero types B:2 and E:2. The objective of this study was to isolate P. multocida from clinical cases and to confirm its identity using polymerase chain reaction (PCR) based approach. Clinical samples of two suspected cases of haemorrhagic septicemia of cattle and buffalo from Mymensingh and Rajshahi districts respectively were collected. Two isolates were isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Based on the results of biochemical tests showed that isolate buffalo and NTT cattle were P. multocidabacteria. These results were in agreement with the findings by Ara et al (2016). In the past study was showed the buffalo NTT isolate is P. multocida type B because it was detected fragment bcbd gene (Puspito, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Based on the results of biochemical tests showed that isolate buffalo and NTT cattle were P. multocidabacteria. These results were in agreement with the findings by Ara et al (2016). In the past study was showed the buffalo NTT isolate is P. multocida type B because it was detected fragment bcbd gene (Puspito, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The blood and impression smears were stained with Giemsa staining for bipolar organisms; isolation was done in 5 % Sheep Blood agar plates (Himedia) for presence of non haemolytic colonies, further streaking was done on BHI agar for dew drop colonies, the pure isolates were tested with biochemical tests like indole, TSI, oxidase and urease tests as described by Hajikolaei et al (2008). In addition to cultural tests, Polymerase chain reaction targeting KTT72 and KTSP61 genes of Pasturella multocida type B as described by Ara et al (2016) with PCR composition of PCR buffer (with 1.5mM Mgcl2) -2 µl, dNTPs (2.5mM each) -2 µl, Primers (20 Picomolar) -2 µl, Taq DNA polymerase (1.5 U) -0.5 µl, template-5 µl, nuclease free water-13.5 µl. PCR conditions are Initial denaturation 95 0 C for 5 min, 35 cycles of denaturation at 95 0 C for 1 min, annealing at 55 0 C for 1 min, extenstion at 72 0 C for 1 min, followed by final extension at 72 0 C for 7min and hold at 4 0 C yielding 620 bp product in 1.5% agarose.…”
Section: Methodsmentioning
confidence: 99%
“…The isolate was initially cultured, isolated on blood agar medium, and identified based on conventional biochemical characteristics. The isolate was confirmed as type B based on molecular methods of PCR using type-specific primers targeting the capsular gene, as was previously described ( 7 , 8 ). For genome sequencing, DNA was isolated using a Wizard genomic DNA kit (Promega Corp., Madison, WI), according to the manufacturer’s instructions.…”
Section: Announcementmentioning
confidence: 99%